The value of urinary sodium assessment in acute heart failure. Issue 2 (14th October 2020) - Tersalvi, Gregorio; Dauw, Jeroen; Gasperetti, Alessio; Winterton, Dario; Cioffi, Giacomo Maria; Scopigni, Francesca; Pedrazzini, Giovanni; Mullens, Wilfried
Abstract: Acute heart failure (AHF) is a frequent medical condition that needs immediate evaluation and appropriate treatment. Patients with signs and symptoms of volume overload mostly require intravenous loop diuretics in the first hours of hospitalization. Some patients may develop diuretic resistance, resulting in insufficient and delayed decongestion, with increased mortality and morbidity. Urinary sodium measurement at baseline and/or during treatment has been proposed as a useful parameter to tailor diuretic therapy in these patients. This systematic review discusses the current sum of evidence regarding urinary sodium assessment to evaluate diuretic efficacy in AHF. We searched Medline, Embase, and Cochrane Clinical Trials Register for published studies that tested urinary sodium assessment in patients with AHF.